Line × tester analysis for combining ability and heterosis in Indian mustard (Brassica juncea) (Journal of Oilseed Brassica, 2026)
Line × tester analysis was carried out to estimate combining ability and heterosis of 18 hybrids developed by crossing 9 lines with 2 testers of Indian mustard. The F1 hybrids along with parental genotypes planted at the experimental farm of ICAR-Directorate of Rapeseed-Mustard Research, Bharatpur, India during 2015-16 were evaluated for twelve characters, including days to flowering, days to maturity, plant height (cm), number of primary & secondary branches / plant, main shoot length (cm), number of siliquae on main shoot, siliqua length (cm), number of seeds per siliqua, 1000-seed weight (g), oil content (%) and seed yield (kg/ha). Analysis of variance revealed sufficient genetic variability among parents, hybrids and parent vs. hybrids for most of the traits. The operation of both additive and non-additive gene actions with predominance of nonadditive gene action was observed in controlling seed yield and contributing traits. Estimates of GCA effects indicated that RH 749, RH 406, Rohini, NRCHB 101 and NPJ 112 were good general combiner. Significant SCA effects for seed yield, 1000-seed weight, number of seeds/ siliqua and other attributing traits in desirable direction were recorded in a series of hybrids and a close association between SCA effects and heterosis was observed amongst the best hybrids identified on the basis of SCA effects. The three hybrids; NRCHB 101/ NPJ 112, RH-749/ NPJ 112 and RH-406/ RRN-727 exhibited high magnitude of better parent, standard parent and mid parent heterosis with highly significant SCA effects and higher per se performance for seed yield and important traits. The high yielding cross combinations can be further exploited for improving the seed yield by development superior genotypes and the parents involved in producing heterotic hybrids shall be converted to well adapted cytoplasmic male sterile or restorer lines.